Recognizing Domestic Violence Against Children by the Competent Police Officers - Spasojević, Aleksandra; Đurđević, Zoran (NBP. Nauka, bezbednosti, policija, 2024)
The paper shows some risk indicators for domestic violence against children, that are concern parents and indicators concern the children. Than it shows analysis of data/results on the sample od 46 competent police officers in Vojvodina with purpose of identification of those indicators. Eighty percent of respondents concider that most frequent risk indicator for violence against children is unfavourable parents behavior. Externalized problems in child behavior are risk indicator that appears always and indicate on violence, by the opinion of 48% respondents. The least present indicator, who appears rarely is sexualized child behaviour (estimated by 63% respondents), which is justified concidering that sexual child is estimated as the rarest form of violence against children. About half of the respondents chose child’s exaggerated reaction when he do something wrong or when points out a mistake to him, as the most frequent indicator of child victim of psychological violence. Although data did not show statistically significant differences in results related to certificate for minors, of respondent concider that competent police officers should also have certificate for minors. As respondents pointed out this need as the biggest systemic complicating work factor in protection of children and as almost half of the officers (22) in this sample did not have this certificate, we point out opinion of autors, that competent police officers as well as police officers of general jurisdiction police, should be specially trained for working with minors, whether thay were victims or witnesses of domestic violence.